Posture-Motor and Posture-Ideomotor Dual-Tasking: A Putative Marker of Psychomotor Retardation and Depressive Rumination in Patients With Major Depressive Disorder - Aftanas, Lyubomir I.; Bazanova, Olga M.; Novozhilova, Nataliya V. (Frontiers in Human Neuroscience, 2018)
Background: Recent studies have demonstrated that the assessment of postural performance may be a potentially reliable and objective marker of the psychomotor retardation (PMR) in the major depressive disorder (MDD). One of the important facets of MDD-related PMR is reflected in disrupted central mechanisms of psychomotor control, heavily influenced by compelling maladaptive depressive rumination. In view of this, we designed a research paradigm that included sequential execution of simple single posture task followed by more challenging divided attention posture tasks, involving concurring motor and ideomotor workloads. Another difficulty dimension assumed executing of all the tasks with eyes open (easy) and closed (difficult) conditions. We aimed at investigating the interplay between the severity of MDD, depressive rumination, and efficiency of postural performance. Method: Compared with 24 age- and body mass index-matched healthy controls (HC), 26 patients with MDD sequentially executed three experimental tasks: (1) single posture task of maintaining a quiet stance (ST), (2) actual posture-motor dual-task (AMT); (3) mental/ imaginary posture-motor dual-task (MMT). All the tasks were performed in the eyes open (EO) and the eyes closed (EC) conditions. The primary dependent variable was the amount of kinetic energy (E) expended for center of pressure deviations (CoPD), whereas the absolute divided attention cost index showed energy cost to the dual-tasking vs. the single posture task according to the formula: ΔE = (EDual-task - ESingle-task). Result: The signs of PMR in the MDD group were objectively indexed by deficient posture control in the eyes closed condition along with overall slowness of fine motor and ideomotor activity. Another important and probably more challenging feature of the findings was that the posture deficit manifested in the ST condition was substantially and significantly attenuated in the MMT and AMT performance dual-tasking activity. A multiple linear regression analysis evidenced further that the dual-tasking energy cost (i.e., ΔE) significantly predicted clinical scores of severity of MDD and depressive rumination. Conclusion: The findings allow to suggest that execution of concurrent actual or imaginary fine motor task with closed visual input deallocates attentional resources from compelling maladaptive depressive rumination thereby attenuating severity of absolute dual-tasking energy costs for